Merger of Burger King and Tim Hortons: analysis of marketing strategies in the quick service restaurants. (25th September 2019) - Musonera, Etienne
Restaurant Brands International Inc. is a Canadian quick service restaurant company. It was created by the merger of Canadian coffee shop restaurant chain Tim Hortons and the US fast food restaurant chain Burger King in 2014 and expanded by the purchase of Popeyes in 2017. The company is the fifth-largest operator of fast food restaurants in the world with more than 25, 000 restaurants operating in over 100 countries under its distinct brands. The merger's primary focus is to expand the international reach of the 'iconic' Tim Hortons brand, and provide financial efficiencies for both companies. In this case analysis, we looked at the past and present situation and addressed business issues facing both Burger King and Tim Hortons. We conducted a systematic case analysis, and used Michael's Five Forces to assess industry attractiveness. We identified problems and issues facing both companies, and we developed a set of strategic alternatives for the new company. We also evaluated and recommended sustainable alternatives marketing strategies to achieve superior results.